Policy Analysis for the Implementation of Electronic-Based Government Systems (SPBE) in the City Government of Depok in Realizing an Open, Participative, Innovative and Accountable City Government - Prihantoro, Edy; Mukodim, Didin; Ohorella, Noviawan Rasyid (Technium Social Sciences Journal, 2021)
Optimization of the use of Information and Communication Technology for each local government varies depending on the availability of infrastructure and human resources. It is necessary to always evaluate and monitor the implementation of government, especially the application of the Electronic Based Government System (SPBE) which is the development of e-government. The research objective is to analyze the implementation of the Electronic Based Government System (SPBE) in the Depok City Government in realizing an open, participatory, innovative, and accountable City Government. The analysis was carried out by looking at the SPBE maturity level index. Measurement of the level of maturity is carried out on the capabilities of technical functions using the e-government maturity model and assesses 3 domains, 7 aspects and 35 indicators contained in an electronic-based government system. The research method used is the interview method with several related officials in the Depok City Government. The results showed that the implementation of an electronic-based government system in the government of Depok City, especially in policy, received a BAIK predicate with a total index value of 2.17. The index shows that the Depok City Government fully supports the implementation of SPBE in the Depok City Government.